The Supreme Administrative Court and the Legislature in Sweden - Larsson, Torvald (Beyond Adjudication : Exploring the Multifaceted Role of Supreme Administrative Courts, 2026)
This contribution discusses relations between the Swedish SAC and the legislature (Riksdag), focusing on how Sweden balances popular sovereignty with judicial independence. The analysis focuses on the legislature's influence on the SAC and – on the other hand – the SAC and its judges’ impact on the legislature, especially the constitutional control of draft legislation carried out by the Council on Legislation, as well as the SAC performing judicial review of legislation. The contribution thoroughly presents the Cementa case, a recent legal dispute highlighting the interplay between judicial review and legislative supremacy. This case illustrates the judiciary's restrained role in challenging legislative decisions. The study concludes that while judicialisation has increased the SAC's prominence, Swedish constitutional law remains grounded in popular sovereignty. This dynamic creates a delicate balance between democratic decision-making and the rule of law, with courts exhibiting cautious deference to legislative authority.
Keywords: Administrative law; Judicial review; Consitutional law; Separation of powers; Förvaltningsrätt; Konstitutionell rätt; Maktdelning; Rättsprövning